Get Answers to all your Questions

header-bg qa

The parabola y^2=\lambda x \text { and } 25\left[(x-3)^2+(y+2)^2\right] =(3 x-4 y-2)^2 are equal, if \lambda is equal to 

Option: 1

1


Option: 2

2


Option: 3

3


Option: 4

6


Answers (1)

best_answer

(d) Let us recall that two parabolas are equal, if the length of their latusrectum are equal.

So, the length of the latusrectum of y^2=\lambda x is \lambda.

The equation of the second parabola is

\begin{aligned} \\25\left\{(x-3)^2+(y+2)^2\right\} =(3 x-4 y-2)^2 \\ \\\Rightarrow \sqrt{(x-3)^2+(y+2)^2}=\frac{|3 x-4 y-2|}{\sqrt{3^2+4^2}} \end{aligned}

Clearly, it represents a parabola having focus at (3,-2) and equation of the directrix as 3 x-4 y-2=0.
\therefore Length of the latusrectum

                               \\=2(\text{distance between focus and directrix})\\ \\=2\left|\frac{3 \times 3-4 \times(-2)-2}{\sqrt{3^2+(-4)^2}}\right|=6

Thus, the two parabolas are equal, if \lambda=6

Posted by

qnaprep

View full answer

JEE Main high-scoring chapters and topics

Study 40% syllabus and score up to 100% marks in JEE